A connection-oriented telecommunications disaster management model using mobile GIS. (23rd November 2005) - Choi, Young B.; Blackburn, Jonathan M.; Seo, Hyewon
Mobile Geographic Information Systems are a versatile extension of traditional GIS and can provide GIS data between the field and the office. This paper addresses the challenges imposed on telecommunications infrastructure management by disaster events. MGIS are presented as tools that provide meaningful real-time communication between field workers and management.